(untitled) (Journal of Economic Research & Business Administration, 2018)
Positive trend on the number of female entrepreneurs in Kazakhstan has been noticed in recent years. Female entrepreneurs are provided with enormous opportunities in countries with transitional economy including Kazakhstan. However, researches provided in developing countries and countries with transitional economies found out that female entrepreneurs are not provided with proper institutional environments, and it serves as a significant problem for them in making a decision to start and/or maintain the business. The barriers exist in the form of heavy tax rates, lack of finance, ineffective banking system, traditional restricted social norms and values and ever-changing legal-system. The aim of this paper was to explore the institutional environment of female entrepreneurs in Kazakhstan and identify how institutional environment influences women’s decision to start and/or maintain their businesses. This theoretical paper with secondary data analyzes investigates whether the institutional environment of women is positively correlated with female entrepreneurial opportunities; and whether this opportunity positively influenced the number of female entrepreneurs in Kazakhstan or not. In order to test those two hypotheses, the researches put the objectives of, firstly, to review the existing literature concerning the institutional environment of female entrepreneurs in Kazakhstan and countries with transitional economies; secondly, to analyze the cases of institutions surrounding and influencing the operations of female entrepreneurs in Kazakhstan; and, lastly, to compare the findings with the theoretical framework and make a decision to accept/reject the hypotheses.